Estabilidade de cor e fluorescência de compósitos resinosos frente a diferentes tipos de bebidas: um estudo in situ - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The aim of this study was to analyze the influence of four types of beverages (water, beer, energy drink and red wine) on the color stability and fluorescence of two resin composites (Filtek Z350XT - 3M; FORMA - Utradent). A total of 160 disc-shaped (6.0 mm x 2.0 mm) composite resin specimens (80 samples each) were made. They were inserted in palatal devices that were used by 05 volunteers. The use of the device was uninterrupted, being removed for the time stipulated for meals (3 hours), oral hygiene and ingestion of other beverages. Each participant ingested 100 ml daily, twice a day (2x50ml) of each beverage (red wine, beer, energy drink and water), for 15 days each, with wash-out intervals of 7 days between the end of the experiment with one beverage and the beginning of the other, totaling 60 days in situ. The initial and final color and fluorescence values of the samples were obtained by means of digital photographs, which were analyzed using the mColorMeter version 2.5.3 program, which provided the CIE-Lab (color analysis) and RGB (fluorescence analysis) color scale values. After verifying the normality of the data by the Shapiro-Wilk test (p>0.05), a two-way ANOVA for color and ANOVA for repeated measures for fluorescence was performed; multiple comparisons between groups were performed by Tukey's post hoc test (α=0.05). In the results, the most pronounced values of color change (ΔE), for both composite resins, occurred with red wine (ΔE=10.5 for Filtek and ΔE=9.90 for Forma) and beer (ΔE=6, 3 for Filtek and ΔE=6.1 for Forma), the lowest values were identified for energy drink (ΔE=2.2 for Filtek and ΔE=2.0 Forma) and water (ΔE=0.9 for Filtek and ΔE=0.7 for Forma). As for fluorescence, divergent levels of fluorescence change occurred between the composites. In both resins, there was a reduction in fluorescence intensity with the red wine beverage and an increase in fluorescence with water (control) and energy. In beer, the Z350 resin suffered an increase in the intensity of this property and Forma suffered a decrease. It was concluded that the daily consumption of 100mls (2x50ml) of the tested beverages, for 15 days each, induced significant changes in the color and fluorescence of the evaluated composites (nanoparticulate and nanohybrid), being the alcoholic beverages red wine and beer the ones that promoted the highest levels of change.
Color stability and fluorescence of composite resins with different types of beverages: an in situ study
Keywords: Resinas dentárias - Testes; Materiais dentários - Testes; Dentes - Clareamento - Testes; CIENCIAS DA SAUDE: ODONTOLOGIA: MATERIAIS ODONTOLOGICOS; Resinas compostas; Estabilidade de cor; Fluorescência; Bebidas